Penerapan Financial Technology (Fintech) pada UMKM Binaan Bank NTT di Sabu Raijua - Yunita Novita Mamo; Fransina W. Ballo; Maria I. H. Tiwu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In today's modern era, humans have a life with all activities that can never be separated from technological developments. One of the technological developments that is currently popular in Indonesia is Financial Technology. Financial Technology (FINTECH) is the latest innovation in the financial service system which is touched by modern technology which can make it easier for Small and Medium Enterprises).to run their businesses with the help of Fintech. The aim of this research is to determine the application of Fintech to Small and Medium Enterprises assisted by Bank NTT in Sabu Raijua and to determine the advantages and disadvantages of implementing Fintech in Small and Medium Enterprises assisted by Bank NTT in Sabu Raijua. This research uses a qualitative research method, which is a research method carried out by means of in-depth interviews in the field, using a phenomenological approach. The data source in this research is primary data obtained directly from Small and Medium Enterprises actors in Sabu Raijua, while secondary data is in the form of interviews, observations and documentation. The research results show that the application of Financial Technology (Fintech) in Small and Medium Enterprises assisted by Bank NTT in Sabu Raijua is experiencing positive developments in line with technological advances and changes in user behavior, ease of access, and transaction security are getting better. However, in its implementation there are several obstacles, namely weak internet connections, elderly Small and Medium Enterprises players find it difficult to understand how to use Financial Technology.